Gaya arsitektur di Middelsburg, negeri Belanda kaitannya dengan Jakarta (Batavia) - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT There are still a lot of buildings in Jakarta from inheritance of Dutch glory period in Indonesia, especially in old-city area and Sunda Kelapa harbour. In this such kind of condition, and then connective between the history of Dutch presence in Jakarta (Verenigde Oost-Indiesche Compagnie) with the presence of existence several buildings in that area, the question raises then : why the buildings appearance and those surroundings look quitely the same with the original ones? How could it happen? After the deeply-observe made, actually the buildings and surroundings in Jakarta (it was called Jakarta, Batavia) were built in concept and performance technics based upon the buildings and surroundings one of the harbour city in Dutch, it's Middelsburg